Effects of benchmarking on the quality of type 2 diabetes care: results of the OPTIMISE (Optimal Type 2 Diabetes Management Including Benchmarking and Standard Treatment) study in Greece. (October 2015) - Tsimihodimos, Vasilis; Kostapanos, Michael S.; Moulis, Alexandros; Nikas, Nikos; Elisaf, Moses S.
Objectives: To investigate the effect of benchmarking on the quality of type 2 diabetes (T2DM) care in Greece. Methods: The OPTIMISE (Optimal Type 2 Diabetes Management Including Benchmarking and Standard Treatment) study [ClinicalTrials.gov identifier: NCT00681850] was an international multicenter, prospective cohort study. It included physicians randomized 3:1 to either receive benchmarking for glycated hemoglobin (HbA1c ), systolic blood pressure (SBP) and low-density lipoprotein cholesterol (LDL-C) treatment targets (benchmarking group) or not (control group). The proportions of patients achieving the targets of the above-mentioned parameters were compared between groups after 12 months of treatment. Also, the proportions of patients achieving those targets at 12 months were compared with baseline in the benchmarking group. Results: In the Greek region, the OPTIMISE study included 797 adults with T2DM (570 in the benchmarking group). At month 12 the proportion of patients within the predefined targets for SBP and LDL-C was greater in the benchmarking compared with the control group (50.6 versus 35.8%, and 45.3 versus 36.1%, respectively). However, these differences were not statistically significant. No difference between groups was noted in the percentage of patients achieving the predefined target for HbA1c . At month 12 the increase in the percentage of patients achieving all three targets was greater in the benchmarking (5.9–15.0%) than in the control group (2.7–8.1%). In the benchmarking group more patients were on target regarding SBP (50.6% versus 29.8%), LDL-C (45.3% versus 31.3%) and HbA1c (63.8% versus 51.2%) at 12 months compared with baseline ( p < 0.001 for all comparisons). Conclusion: Benchmarking may comprise a promising tool for improving the quality of T2DM care. Nevertheless, target achievement rates of each, and of all three, quality indicators were suboptimal, indicating there are still unmet needs in the management of T2DM.